Viralitas Lato-Lato dalam Inovasi Pembelajaran di Pondok Pesantren Nurul Ichsan Bontang - Rosadi, Khumaini; Wahyuni, Rika (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2023)
The current viral game phenomenon, lato-lato. Consisting of two hard solid plastic balls a number of cold meatballs or ping pong balls with a small thin rope. You swing your finger up and down and the pendulum has to be balanced to produce a rattling sound. Knock tok tok tok tok.The rhythm is also good, many students at the Nurul Ichsan Bontang Islamic Boarding School play it too, so there's nothing wrong with combining it with hadroh blows for prayer. In addition to variations in the treasures of maulidan prayers. Increasingly adding to learning innovations at the Nurul Ichsan Islamic Boarding School.So not all children's play is negative. Sometimes it is positive and can become a new branch of e-sport, even a new knowledge.